Risk Factor Analysis of Lamentation of Musculoskeletal Disorders (MSDs) in Palm Oil Harvester Workers in South Labuhan Batu District - Ayu Ardillah; Putra Apriadi siregar; Syafran Arrazy (Universitas Islam Negeri Sumatera Utara, Medan, 2024)
The palm oil harvesting process is still carried out manually, relying on human power and is carried out repeatedly, potentially causing complaints of Musculoskeletal Disorders (MSDs). Data collection was carried out in January - February 2024 among palm oil harvesting workers in Labuhan Batu. The sample selection technique involved a total sampling of 58 oil palm harvesters. Data was collected using the Nordic Body Map (NBM) questionnaire through observation of palm oil harvesting activities. Data processing and analysis uses 4 processes, namely coding, editing, data entry and cleaning. This study uses an analysis carried out to assess the risk level of musculoskeletal disease (MSDs) based on many variables of age, body weight, years of work and duration of work. With the help of SPSS 26 using the correlation test, there is abnormal data on 4 variables, so the Spearman correlation test is used to determine the strength of the relationship between the variables. In the statistical test results, it was found that the pvalue was 0.001 < 0.05, which means there is a relationship between age and MSDs complaints, the statistical test results showed that the pvalue was 0.005 < 0.05,. Research shows the importance of musculoskeletal conditions throughout life, especially in palm oil harvesting workers who are susceptible to complaints of MSDs in various parts of the body. The factors age, length of service and duration of work influence this complaint, while body weight is not significant. The researchers' recommendations include work posture training and the use of assistive devices to reduce the risk of MSDs, as well as supporting the development of more effective occupational health and safety policies, especially in the palm oil industry. Keywords: Complaint, Disturbance, Musculoskeletal, Palm Oil Harvester, Worker